2017
DOI: 10.3390/su9112027
|View full text |Cite
|
Sign up to set email alerts
|

Big Social Network Data and Sustainable Economic Development

Abstract: New information technologies have led to the rapid and effective growth of social networks. The amount of data produced by social networks has increased the value of the big data concept, which is one of the popular current phenomena. The immediate or unpredictable effects of a wide array of economic activities on large masses and the reactions to them can be measured by using social media platforms and big data methods. Thus, it would be extremely beneficial to analyze the harmful environmental and social imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 34 publications
1
26
0
1
Order By: Relevance
“…The efficiency scores in Table 3 reveal a substantial gulf between fully-efficient organizations and all other organizations. This finding highlights the importance of innovation and sustainable development as measures to improve performance and thereby achieve greater efficiency [15,32,67].…”
Section: Analysis Of Economic Efficiencymentioning
confidence: 97%
See 1 more Smart Citation
“…The efficiency scores in Table 3 reveal a substantial gulf between fully-efficient organizations and all other organizations. This finding highlights the importance of innovation and sustainable development as measures to improve performance and thereby achieve greater efficiency [15,32,67].…”
Section: Analysis Of Economic Efficiencymentioning
confidence: 97%
“…Scholars have shown that these technologies contribute to performance in terms of better productivity, profitability, process development, market value, and sustainability [13][14][15][16][17]. To achieve these results, however, companies must adopt and integrate the tools that the Internet has to offer by following a carefully planned strategy [18].…”
Section: Contextual Framework and Working Hypothesismentioning
confidence: 99%
“…Can and Alatas [25] argued that a high source of big data provided by user interactions on social network platforms created a new concept (big social network data) which, through its effective use of specific technologies, leads to a sustainable development of a business.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Big data can be useful to enterprises from all industries in identifying customer needs, improving productivity, and gaining a competitive advantage. More importantly, big data plays a new and important role in achieving sustainable economic development [12]. Sustainability consists of three aspects: environmental, economic, and social sustainability [13].…”
Section: Introductionmentioning
confidence: 99%